Działalność Sodalicji Mariańskiej w kolegiach bazyliańskich na ziemiach Rzeczypospolitej w XVIII i XIX wieku - Lorens, Beata (Archiwa, Biblioteki i Muzea Kościelne, 2020)
The aim of this article is to present the activity of the Sodality of Our Lady functioning in public secondary schools run by the Basilian Order in eastern Poland in the 18th and the 19th centuries. The sources of the information were the books of the congregation, inventories of the monasteries and educational records stored in Polish and Ukrainian archives and printed reports of school visitations conducted by the Commission of National Education. We managed to find traces of the activity of the Sodality of Our Lady in 10 Basilian colleges, out of 20 functioning in the 18th century in the Polish-Lithuanian State. The activity of three schools- Buczacz, Owrucz and Podubiś- is the best documented one in sources. As far as the organizational pattern is concerned, these congregations followed the example of societies functioning in the colleges run by Jesuits. The students of the Sodality were distinguished by very good results in learning, impeccable behavior and devotion. The Marian Congregation helped to deepen faith and they paid special attention to the cult of Mary. They also prepared young people from the gentry background to take part in public life. The Congregation was a very important element in the educational process conducted in the public monastic schools.